Changes in contrast transit times on digital subtraction angiography post-Pipeline Embolization Device deployment. Issue 2 (April 2017) - Hussein, Ahmed E; Linninger, Andreas; Shakur, Sophia F; Charbel, Fady T; Hsu, Chih-Yang; Charbel, Fady T; Alaraj, Ali
It is postulated that hemodynamic changes occur in the distal vascular bed post-deployment of Pipeline Embolization Devices (PEDs). In this paper, we evaluate changes in the contrast transit times (TTs) on digital subtraction angiography (DSA) post-PED interventions. DSA films were analyzed using custom-made software for the time-density relationship at baseline and compared to post-PED deployment. All analyses were performed within the middle cerebral artery (MCA) M1 segment. Analyses included TT10%–100% (time needed for the contrast to change from 10% image intensity to 100%), TT100%–10%, and TT25%–25% . Forty-four patients were included. We found a significant decrease in TT10%–100% (2.79 to 2.24 seconds, p < 0.001) post-PED. There was a significant correlation between the percentage change in TT100%–10% and aneurysm size ( p = 0.02). There was also a significant decrease in TT25%–25% (7.07 to 6.41 seconds, p = 0.02) post-PED. Moreover, there was a significant correlation between the absolute or percentage changes in TT25%–25% and aneurysm size (rho = 0.54, p = 0.05 and rho = 0.29, p = 0.05, respectively). Statistically significant distal intracranial hemodynamic changes occur post-PED deployment. These hemodynamic changes appear to be more pronounced with large and giant aneurysms.